Hydrothermal synthesized AgNbO3 powders: Leading to greatly improved electric breakdown strength in ceramics. Issue 15 (December 2020) - Wang, Jing; Wan, Xinhong; Rao, Yu; Zhao, Lei; Zhu, Kongjun
Abstract: Silver niobate AgNbO3 ceramics have been regarded as a promising lead-free material for energy storage applications. In present work, pure and fine AgNbO3 powders were successfully fabricated via the hydrothermal method using AgNO3 as the raw material. It is found that the reaction products show strong dependence on the molar ratio of NH4 HF2 :AgNO3 :Nb2 O5, pH value and reaction time. Pure AgNbO3 powders were obtained when the process conditions are 3NH4 HF2 :2AgNO3 : x Nb2 O5 with x ≤0.85 or y NH4 HF2 :2AgNO3 :1Nb2 O5 with y = 4–5, pH = 5 and reaction time t ≥ 10 h. Benefitting from the hydrothermal synthesised AgNbO3 powders, AgNbO3 ceramics with fine-grain of ∼3.4 μm were obtained. The fine-grain leads to increased electric breakdown strength E b up to 250 kV/cm, which is the highest among the pure AgNbO3 ceramics to our best knowledge. The further enhancement in E b and recoverable energy density could be highly anticipated if the antiferroelectric phase could be stabilized.